Tumor site, stage, and receptor-specific efficacy of radiation therapy in Asian breast cancer patients aged 60 years and older: A SEER database survival analysis incorporating clinicopathological features and nomograms - Qixin Mao; Haonan Han; Lianfang Li; Shanqing Liu; Yong Li; Yan Shen; Leiming Guo; Liming Xu (Breast)
Purpose: This study evaluates the survival benefits of radiation therapy (RT) in elderly (≥60 years) Asian breast cancer patients focusing on tumor site, stage, and receptor status using SEER data. And aims to provide a nuanced understanding of how RT impacts survival outcomes in this demographic, particularly across varying tumor stages and receptor statuses. Methods: We analyzed 47,868 elderly (≥60 years) Asian patients from the SEER database (2000–2021). Survival outcomes were assessed using Kaplan-Meier analysis, Cox regression models, and nomograms. Multivariate analyses quantified RT efficacy across tumor sites (central, axillary tail), hormone receptor status (ER/PR, HER2), and stages (I–IV). Results: RT improved median overall survival (OS) (17.5 vs. 13.4 years; hazard ratio [HR] = 0.54, p < 0.001), with consistent benefits across delivery methods. Axillary tail tumors showed the greatest survival gain (64.2 % OS improvement, HR = 0.36). ER/PR-positive patients derived significant benefit (HR = 0.48), unlike HER2-positive cases (p = 0.12). Stage III patients experienced maximal survival improvement (HR = 0.41), while stage IV showed marginal benefits (HR = 0.89). Age-stratified analyses confirmed benefits across all groups (60–69, 70–79, ≥80 years). Conclusion: RT confers significant survival benefits in elderly (≥60 years) Asian breast cancer patients, with pronounced efficacy observed in axillary tail tumors and stage III disease. ER/PR-positive tumors exhibit enhanced treatment responsiveness, while HER2 status remains non-predictive of therapeutic outcomes. However, limited efficacy in stage IV disease underscores the necessity for alternative management strategies in advanced-stage settings. These findings emphasized personalizing RT guided by tumor biology and staging, while carefully considering comorbidities and treatment-related toxicities in geriatric oncology populations.